The Relationship Between Levels of Mathematics Anxiety and Mathematics Learning Outcomes of Upper Grade Elementary School Students in Sidoarjo: Hubungan Antara Tingkat Kecemasan Matematika dengan Hasil Belajar Matematika Siswa Kelas Atas Sekolah Dasar di Sidoarjo - Pratama, Riska Hani; Affandi, Ghozali Rusyid (Universitas Muhammadiyah Sidoarjo, 2023)
This study aims to determine the relationship between Mathematics Anxiety Levels with Mathematics Learning Outcomes in upper grade elementary school students in Sidoarjo. The type of research used in this study is a quantitative method with a correlational approach. The population in this study were 185 students. The sampling technique used is the saturated sampling technique. Data retrieval using a Likert model scale, namely the Mathematical Anxiety scale with a reliability of 0.808. And the Final Value of Mathematics Subjects obtained from secondary data in the form of notes (reports) of mathematics learning outcomes. The analysis in this study results in the correlation coefficient (rxy) = - 0.173 and the significance is 0.019 > 0.05, which indicates that the negative hypothesis is accepted. So the results of this study indicate a negative direction between the level of mathematics anxiety and Mathematics Learning Outcomes. That is, the higher the level of mathematics anxiety, the lower the mathematics learning outcomes for upper grade elementary school students in Sidoarjo.